High-mannose type N-glycan binding specificity of a novel lectin from the red alga (Betaphycus gelatinus) - Hung, Le Dinh; Thi Doan Thuc, Le (Vietnam Journal of Biotechnology, 2020)
The red alga, Betaphycus gelatinus is one of carrageenan sources in the world. The lectin from the red alga B. gelatinus was isolated by a combination of aqueous ethanol extraction, ethanol precipitation, ion-exchange chromatography and gel filtration chromatography and was designated as BGL after the specific name of alga. Lectin gave a single band with molecular mass of about 19,000 Da in both non-reducing and reducing SDS-PAGE conditions, therefore lectin exists in monomer form. The hemagglutination activities of BGL were stable over a wide range of pH from 3 to 10, temperature up 60 oC and not affected by either the presence of EDTA or addition of divalent cations, indicating that lectin requires no metal for biological activity. The hemagglutination activities of BGL were not inhibited by monosaccharides and glycoproteins, D-glucose, D-mannose, D-galactose, D-xylose, N-acetyl-galactosamine, N-acetyl-glucosamine, N-acetyl-neuraminic acid, N-acety-D-mannosamine, transferrin and fetuin, but strongly inhibited by glycoproteins bearing high-mannose type N-glycan, such as yeast mannan and porcine thyroglobulin. Lectin BGL is specific for N-glycans and may recognize terminal (α1–3) or (α1–6)-linked mannose residues in structure Man(α1-6)[Man(α1-3)]Man(α1-6)[Man(α1-3)]Man(β1-4)GlcNAc(β1-4)GlcNAc of N-glycans. High-mannose type N-glycan binding specificities of this lectin highly resemble with those of the anti-cancer, anti-virus and anti-bacteria lectins from the red algae, carrageenophytes, including Eucheuma serra (ESA-2), Eucheuma denticulatum (EDA-2), Kappaphycus striatum (KSA-2), Kappaphycus alvarezii (KAA-1 and KAA-2) and Solieria filiformis (SfL1 and SfL2). The red alga B. gelatinus could promise to be a good source of valuable lectins for application in biochemistry and biomedicine.